Computer-assisted image-based risk analysis and planning in lung surgery - a review - Krass, Stefan; Lassen-Schmidt, Bianca; Schenk, Andrea (Frontiers in Surgery, 2022)
In this paper, we give an overview on current trends in computer-assisted image-based methods for risk analysis and planning in lung surgery and present our own developments with a focus on com-puted tomography (CT) based algorithms and applications. The methods combine heuristic, knowledge based image processing algorithms for segmentation, quantification and visualization based on CT images of the lung. Impact for lung surgery is discussed regarding risk assessment, quantitative assessment of resection strategies, and surgical guiding. In perspective, we discuss the role of deep learning based AI methods for further improvements.